Sodium chromo-glycate and palmitoylethanolamide: A possible strategy to treat mast cell-induced lung inflammation in COVID-19. (October 2020) - Gigante, Antonio; Aquili, Alberto; Farinelli, Luca; Caraffa, Alessandro; Ronconi, Gianpaolo; Enrica Gallenga, Carla; Tetè, Giulia; Kritas, Spyros K.; Conti, Pio
Abstract: A novel human coronavirus SARS‐CoV‐2 (also referred to as CoV-19) that emerged in late 2019 causes Covid-19 disease a respiratory tract infection which provokes about 4 million deaths per year. Unfortunately, to date, there is no specific antiviral treatment for COVID-19. Mast cells (MCs) are immune cells implicated in the pathogenesis of viral infections, where they mediate inflammation. Microbes, including virus, activate MCs through TLR releasing chemical pro-inflammatory compounds and cytokines. Although, in biomedical literature there are only few reports on MCs activation by SARS-CoV-2 infection. The production of pro-inflammatory cytokines by MC viral activation leads to increase pulmonary inflammation and fibrosis. Sodium Chromo-Glycate (SCG) described as a MC stabilizer, prevents the release of inflammatory chemical compounds, improve mouse survival and respiratory pathological changes in lung viral infection and suppresses inflammation. Furthermore, palmitoylethanolamide (PEA) a nuclear factor agonist, an endogenous fatty acid amide, which exerts a variety of biological effects, related to chronic inflammation and pain, is involved also in MCs homeostasis with an inhibitory and protective effect on the respiratory tract during viral infections. Here, we hypothesize for the first time, that SCG and/or PEA suppress MC activation and pro-inflammatory mediators release, playing an anti-inflammatory therapeutic role in the inflamed lung of patients with COVID-19.